Analisis Fraud Pentagon Terhadap Kecurangan Laporan Keuangan Pada Sektor Perusahaan Manufaktur - Delviana Dama Yanti; Munari Munari (Akuisisi: Jurnal Akuntansi, 2021)
The purpose of this research is to see the effect of pentagon fraud that proxied by financial targets, nature of the industry, quality of external auditors, change of auditors, number of CEOs who frequently detect fraud in financial statements. Financial statement fraud in this study was measured using the proxies of Return on Assets, Receivables, selection of audit services at public accounting firms, changes in public accounting firms, changes in directors, and the number of CEO photos. The population in research study are use manufacturing companies who listed on the Indonesia Stock Exchange (BEI) in 2017-2019. This research uses a purposive sampling technique so, there are 48 financial reports from 25 manufacturing companies. The analytical method used in this research is multiple linear regression analysis with SPSS version 20. The results of this research indicate that financial targets, nature of industry, quality of external auditors and the number of CEOs who often don’t have a significant effect in the handling of fraudulent financial statements. Meanwhile, changes in auditors and changes in direction have a significant effect from pentagon fraud side on fraudulent financial statements.Tujuan penelitian ini adalah untuk menganalisis pengaruh moderasi locus of control, faktor-faktor yang mempengaruhi sistem informasi keuangan pada kantor kecamatan di kota Semarang. Populasi penelitian ini adalah 16 Kantor Kecamatan di Kota Semarang dan diperoleh 54 kuesioner, kemudian dianalisis analisis regresi moderasi (MRA). Dari hasil penelitian pengaruh Locus of Control Moderation terhadap Efektifitas Sistem Informasi Keuangan pada Kantor Kecamatan Kota Semarang Provinsi Jawa Tengah diperoleh hasil penelitian hipotesis pertama yaitu pengaruh manajemen puncak terhadap efektivitas sistem informasi, untuk menguji pengaruh kepuasan pengguna terhadap efektivitas sistem informasi, untuk menguji pengaruh budaya organisasi terhadap efektivitas sistem informasi. Efektivitas sistem informasi, untuk menguji pengaruh locus of control terhadap hubungan antara manajemen puncak terhadap efektivitas sistem informasi, untuk menguji pengaruh locus of control antara kepuasan pengguna terhadap efektivitas sistem informasi dari hasil penelitian menghasilkan pengaruh yang positif dan signifikan.